Concurrent Validity of the Shedler-Westen Assessment Method and the Millon Clinical Multiaxial Inventory-IV in a Non-Clinical Sample from the Iranian Oil Industry - Ali Bakhshian, Sodeh; Sarafraz, Reza; Belyad, Mohamad Reza; Kamkari, Kambiz; Haji Heydari, Mehdi (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The study aims to evaluate the concurrent validity of the Shedler-Westen Assessment Procedure (SWAP-200) and the Millon Clinical Multiaxial Inventory-IV (MCMI-IV) in a non-clinical sample from the Iranian oil industry. Methods and Materials: The research utilized Pearson’s product-moment correlation model to assess the relationship between the scales of the Shedler-Westen Assessment Procedure and the Millon Clinical Multiaxial Inventory-IV. The study sample consisted of employees from the Iranian oil industry who participated in a psychological evaluation for managerial or contract promotion purposes. Findings: The results demonstrated significant positive correlations between the scales of the SWAP-200 and the MCMI-IV, with correlation coefficients of 0.60 or higher at α = 0.01 and α = 0.05 levels. This indicates that both tools have strong concurrent validity in measuring personality disorders. Conclusion: The study confirms that the Shedler-Westen Assessment Procedure and the Millon Clinical Multiaxial Inventory-IV exhibit concurrent validity in a non-clinical sample, supporting their effectiveness in assessing personality disorders in organizational contexts.